Exploring the effect of greenhouse covering cultivation on the changes of sensory quality and flavor substances of green tea - Qian Wang; Meng Li; Jie Wang; Xueming Ma; Lei Liu; Peiqiang Wang; Jianhui Hu; Xinfu Zhang; Fengfeng Qu (Food Chemistry: X)
To protect tea plant (Camellia sinensis (L.) O. Kuntze) from freezing injury, plastic greenhouse covering is widely used in northern tea areas of China. Currently, there was few researches about the effect of greenhouse covering on tea quality. Our results showed greenhouse covering increased tea yield, changed leaf phenotype and decreased green tea quality. Further analysis revealed greenhouse increased the content of soluble sugars and decreased the content of EGCG and 14 amino acids. Besides, there were 223 differential volatile components were identified in green tea produced by fresh leaves with plastic greenhouse covering (GT) and green tea produced by fresh leaves without plastic greenhouse covering (TT). 81 key aroma components were contributors to the bean-like aroma of TT. 98 key aroma components contributed to the clean aroma of GT. Based on these results, the flavor wheels were constructed, providing a visual presentation of flavor between TT and GT.